Improvement of Sungai Sebulung Water Quality Using Effective Microorganism - Firdaus, Ahmad; Azman, Shamila; ., . (International Journal of Engineering and Technology, 2018)
Effective Microorganism (EM) is a practical and less costly method to enhance water quality. Sungai Sebulung is one of the rivers in Malaysia that have been treated using EM. This study has been carried out to find the effectiveness of EM and its suitability to the condition of Sungai Sebulung. This study will also evaluate Water Quality Index (WQI) of the river. The WQI of Sungai Sebulung is 56.2 and can be classified as a Class III. The average concentration of DO, BOD, COD, AN and TSS at Sungai Sebulung were 3.88 mg/L, 10.7 mg/L, 54 mg/L, 3.78 mg/L and 26.2 mg/L respectively. The result obtained shows the quality of Sungai Sebulung is the same compared to 2016